The phylogenetic distribution of ultraviolet sensitivity in birds - Ödeen, Anders (BioMed Central, 2013)
BACKGROUND: Colour vision in birds can be categorized into two classes, the ultraviolet (UVS) and violet sensitive (VS). Their phylogenetic distributions have traditionally been regarded as highly conserved. However, the complicated nature of acquiring spectral sensitivities from cone photoreceptors meant that until recently, only a few species had actually been studied. Whether birds are UVS or VS can nowadays be inferred from a wide range of species via genomic sequencing of the UV/violet SWS1 cone opsin gene. RESULTS: We present genomic sequencing results of the SWS1 gene from 21 avian orders. Amino acid residues signifying UV sensitivity are found in the two most important spectral tuning sites 86 and 90 of Pteroclidiformes and Coraciiformes, in addition to the major clades, Palaeognathae, Charadriiformes, Trogoniformes, Psittaciformes and Passeriformes, where they where previously known to occur. We confirm that the presumed UVS-conferring amino acid combination F86, C90 and M93 is common to Palaeognathae and unique to this clade, despite available spectrometric evidence showing the ostrich retina to be VS. CONCLUSIONS: By mapping our results together with data from previous studies on a molecular phylogeny we show that avian colour vision shifted between VS and UVS at least 14 times. Single nucleotide substitutions can explain all these shifts. The common ancestor of birds most likely had a VS phenotype. However, the ancestral state of the avian SWS1 opsin’s spectral tuning sites cannot be resolved, since the Palaeognathae are F86, C90 while the Neognathae are ancestrally S86, S90. The phylogenetic distribution of UVS and VS colour vision in birds is so complex that inferences of spectral sensitivities from closely related taxa should be used with caution.